What it means to say, ‘a person is a person through other persons’: Ubuntu through humanistic-existential lenses of transactional analysis - Chigangaidze, Robert, K. (Taylor & Francis, 2022)
Ubuntu is a relational philosophy which is best known through the axiom, ‘umuntu ngubuntu ngabantu’ a person is a person through other persons. Transactional Analysis (TA) as a relational theory as well, is used in this paper, to expand on the understanding of the Ubuntu proverb. Existential life position, ‘I’m OK, You’re OK’ and constructs of TA such as transgenerational scripts, stroking and physis are utilized to expand on the meaning of ‘umuntu ngubuntu ngabantu.’ Based on the provisions of TA, the African axiom is connected to aspects of child development, parenting, communication, sustainable development, spirituality and ecological social work. Significantly, the discourse argues that ‘umuntu ngubuntu ngabantu’ should never be divorced from the values of the African philosophy which include kindness, forgiveness, hospitality, humanness, social justice, human rights, social solidarity, liberty and other positive virtues. Thus, this paper is a plea for a TA and ubuntu informed social work practice that can entangle humanity from the negative transactional scripts whilst reinforcing the positive ones. To its end, the paper questions what this generation will be remembered for when it becomes the living dead (ancestors).